Teachers' beliefs and practices of Intercultural Communication Competence in teaching and learning English: A survey at a local high school in Phu Tho province = Hiểu biết của giáo viên đối với năng lực giao tiếp liên văn hóa trong dạy và học tiếng Anh : - Hoàng, Thị Hiền, 1984- (2020)
This study was done aiming at finding out how teachers perceive Intercultural Communication Competence (ICC) in teaching and learning English. Moreover, how their beliefs are integrated in their teaching practices were also the subjects to point out. To fulfill the abovementioned objectives, the qualitative methodologywas utilized, and the data mostly based on semi-structured interviews with six teachers of English at a local high school in a mountainous provincewere synthesized and analyzed. The results of the study, in summary, showed that most of the teacherssurveyed have poor understanding of ICC, which results in their confusion about ways to improve students’ ICC. Those beliefs and practices may be influenced by some different factors such as teachers’ lack of experience, materials,... As a result, suggestions and recommendations were investigated so as to deal with the problems. Though the limitations were unavoidable, the study was expected to be beneficial to teachers, students, and researchers of the related subjects.